Apolipoprotein A‐IV concentrations and clinical outcomes in a large chronic kidney disease cohort: Results from the GCKD study. (4th January 2022) - Schwaiger, Johannes P.; Kollerits, Barbara; Steinbrenner, Inga; Weissensteiner, Hansi; Schönherr, Sebastian; Forer, Lukas; Kotsis, Fruzsina; Lamina, Claudia; Schneider, Markus P.; Schultheiss, Ulla T.; Wanner, Christoph; Köttgen, Anna; et al.
Abstract: Background: Chronic kidney disease (CKD) represents a chronic proinflammatory state and is associated with very high cardiovascular risk. Apolipoprotein A‐IV (apoA‐IV) has antiatherogenic, antioxidative, anti‐inflammatory and antithrombotic properties and levels increase significantly during the course of CKD. Objectives: We aimed to investigate the association between apoA‐IV and all‐cause mortality and cardiovascular outcomes in the German Chronic Kidney Disease study. Methods: This was a prospective cohort study including 5141 Caucasian patients with available apoA‐IV measurements and CKD. The majority of the patients had an estimated glomerular filtration rate (eGFR) of 30–60 ml/min/1.73m 2 or an eGFR >60 ml/min/1.73m 2 in the presence of overt proteinuria. Median follow‐up was 6.5 years. The association of apoA‐IV with comorbidities at baseline and endpoints during follow‐up was modelled adjusting for major confounders. Results: Mean apoA‐IV concentrations of the entire cohort were 28.9 ± 9.8 mg/dl. Patients in the highest apoA‐IV quartile had the lowest high‐sensitivity C‐reactive protein values despite the highest prevalence of diabetes, albuminuria and the lowest eGFR. Each 10 mg/dl higher apoA‐IV translated into lower odds of prevalent cardiovascular disease (1289 cases, odds ratio = 0.80, 95% confidence interval [CI] 0.72–0.86, p = 0.0000003). During follow‐up, each 10 mg/dl higher apoA‐IV was significantly associated with a lower risk for all‐cause mortality (600 cases, hazard ratio [HR] = 0.81, 95% CI 0.73–0.89, p = 0.00004), incident major adverse cardiovascular events (506 cases, HR = 0.88, 95% CI 0.79–0.99, p = 0.03) and death or hospitalizations due to heart failure (346 cases, HR = 0.84, 95% CI 0.73–0.96, p = 0.01). Conclusions: These data support a link between elevated apoA‐IV concentrations and reduced inflammation in moderate CKD. ApoA‐IV appears to be an independent risk marker for reduced all‐cause mortality, cardiovascular events and heart failure in a large cohort of patients with CKD. Abstract :